PENGUKURAN KINERJA SUPPLY CHAIN MANAGEMENT MENGGUNAKAN MODEL SCOR PADA PT. XYZ - Fikriyani; Saryatmo, Mohammad Agung; Andres (Jurnal Ilmiah Teknik Industri, 2025)
In the oil and gas drilling services sector, PT. XYZ faces obstacles in the form of late delivery of materials from suppliers which can affect operational efficiency and result in downtime. The purpose of this study is to evaluate SCM performance by applying the SCOR model and the AHP approach to identify areas that need improvement. Calculated using the SCOR model, there are five main processes, namely plan, source, make, deliver and return. After conducting a questionnaire, 17 performance indicators were selected with the attributes of reliability, responsiveness, and asset. The AHP approach was applied to give weight to the performance indicators to identify the main criteria and priorities. With a performance value of 87.41, the measurement results indicate that PT. XYZ supply chain management is running quite well. There are 2 (two) of the 17 performance indicators measured, namely adherence to production and number of touble machines, that need to be improved.